(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Based on the data of the Samarkand city IDCH, a comparative analysis of clinical and laboratory data and serological research results was conducted in 225 patients with the most severe course of brucellosis with polyfocal lesions in the sub- and decompensated stages. . The syndromes common in patients with primary chronic brucellosis and secondary chronic brucellosis and their symptoms are analyzed.